Determinan Minat Keprilakuan Pengguna E-Samsat di Kota Denpasar dengan Pendekatan UTAUT - Yustina, Ni Luh Feby Millennia; Baridwan, Zaki (E-Jurnal Akuntansi, 2023)
E-Samsat is one of the implementations of e-government which is intended to provide convenience for the public in carrying out tax obligations, especially paying motor vehicle taxes. This study aims to examine and analyze the determinants of interest in using the e-samsat system for motor vehicle taxpayers in Denpasar City using the UTAUT theory approach. Two personal factors, namely self-efficacy in using the web system and perceptions of security control, are also added as constructs that influence the intention to use the e-samsat system. A total of 400 respondents were collected using a questionnaire survey method with purposive sampling technique. Data analysis used the linear regression method with the SPSS version 25 application. The results showed that the variable effort expectations, performance expectations, self-efficacy in using the web system and perceptions of security control had a positive effect on the intention to use e-samsat. However, social influence was not found as a construct that had an effect on the intention to use e-samsat. Keywords: E-government; E-Samsat; UTAUT; Intention to Use System